Academic Text Quality Improvement By English Department Students of University of Mataram : A Study on Pre-Editing of Google Neural Machine Translation - Baiq Chunafa Diza Farhana; Baharuddin Baharuddin; Lalu Ali Wardana; Santi Farmasari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2023)
This study aims to determine the quality of students in pre-editing academic text input to GNMT. The participants in this study were students of the English Language Education Study Program, Faculty of Teacher Training and Education, the University of Mataram, who took the